2014
DOI: 10.1038/mp.2013.190
|View full text |Cite
|
Sign up to set email alerts
|

Stress and glucocorticoids promote oligodendrogenesis in the adult hippocampus

Abstract: Stress can exert long-lasting changes on the brain that contribute to vulnerability to mental illness, yet mechanisms underlying this long-term vulnerability are not well understood. We hypothesized that stress may alter the production of oligodendrocytes in the adult brain, providing a cellular and structural basis for stress-related disorders. We found that immobilization stress decreased neurogenesis and increased oligodendrogenesis in the dentate gyrus (DG) of the adult rat hippocampus, and that injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
170
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(177 citation statements)
references
References 81 publications
(75 reference statements)
6
170
0
1
Order By: Relevance
“…22,47 It may be that the hippocampus is vulnerable to a variety of environmental factors, including obstetric complications 48 and stress, 49 varying according to the hormonal milieu 50 that is then linked to schizophrenia. 51 We confirmed our hypothesis of an association between low birth weight and hypoxia and smaller whole brain, white matter and grey matter volumes. It is accepted that perinatal obstetric complications have an effect on brain structure, function 52 and neurodevelopment.…”
Section: Unique Environmental Effectssupporting
confidence: 79%
“…22,47 It may be that the hippocampus is vulnerable to a variety of environmental factors, including obstetric complications 48 and stress, 49 varying according to the hormonal milieu 50 that is then linked to schizophrenia. 51 We confirmed our hypothesis of an association between low birth weight and hypoxia and smaller whole brain, white matter and grey matter volumes. It is accepted that perinatal obstetric complications have an effect on brain structure, function 52 and neurodevelopment.…”
Section: Unique Environmental Effectssupporting
confidence: 79%
“…Significant difference between stress control and stress treated with honey ( ♣ P < .05). both glucocorticoid exposure and oxidative stress may induce neuronal oxidative stress through enhanced mitochondrial respiration and oxidative phosphorylation [50], and promote gliogenesis over neurogenesis in hippocampal neural stem cell progenitors [51,52]. Correspondingly, we demonstrated that the stressed rats possessed a lower number of pyramidal neurons in the hippocampus as well as in the mPFC compared to the nonstressed rats.…”
Section: Discussionmentioning
confidence: 57%
“…A recent study has shown that acute CORT treatment (for 7 days) shifts the balance of cell types produced towards fewer neurons and more oligodendrocytes, and has suggested the possibility that this shift may underlie behavioral effects of CORT treatment (Chetty et al, 2014). We note that here we did not observe a significant effect of CORT treatment on the percent of BrdU-positive cells that are colabeled with the neuronal marker NeuN (Figure 3d), possibly because BrdU was injected 4 weeks before the onset of CORT treatment (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…While neurons make up the majority of adult-born cells labeled with BrdU in the hippocampus, stem cells, and astrocytes and potentially even oligodendrocytes (Chetty et al, 2014) are also found. To determine the proportion of neurons produced, colabeling was assessed between BrdU and the mature neuronal marker neuronal nuclei (NeuN).…”
Section: Genetic Deletion Of Bax Increases Adult Hippocampal Neurogenmentioning
confidence: 99%